KUAT LEKAT TULANGAN BAMBU PETUNG DAN BAMBU TALI DALAM BETON NORMAL - Sudarsana, I Ketut; Putra, Dharma; Puryandhari, I Gusti Ayu Putu Wegie (Jurnal Ilmiah Teknik Sipil; Jurnal Ilmiah Teknik Sipil, Vol. 24, No. 1, Januari 2020DO - 10.24843/JITS.2020.v24.i01.p06, 2020)
This research was conducted to obtain the bond strength between the varnished bamboo in concrete with the variation in embedded length of reinforcement in the concrete and the type of bamboo. The bamboo used is Petung bamboo from Sidemen Village, Karangasem and Tali bamboo from Manggisari Village, Negara. The specimens were made in the form of bamboo Petung and Tali reinforcement with dimensions of width 15 mm and thickness of 5 mm embedded into a concrete cube of 150 mm x 150 mm x 150 mm with a compressive strength of 20 MPa. Reinforcement planted at the center of the cube as deep as 100 mm and 75 mm. Pull out test was carried out with a Universal Testing Machine (UTM). To find out the tensile strength of bamboo, tensile tests were carried out on bamboo reinforcement with and without nodes having dimensions of 5 mm width and 5 mm thick for Petung bamboo, and 5 mm width and 3 mm thick for Tali bamboo. The results of tensile strength of Petung bamboo with and without nodes were 155.14 MPa and 268.08 MPa respectively. Whereas the tensile strength of Tali bamboo with and without nodes was 138.42 MPa and 182.13 MPa respectively. The results of bond test show that the average value of bond stress of the Petung bamboo with the embedded length of 100 mm with and without nodes was 1.44 MPa and 1.34 MPa, espectively, while the embedded length of 75 mm with and without nodes was 2.61 MPa and 1.74 Mpa, respectively. The Average bond stress of the Tali bamboo with the emebedded length of 100 mm with nodia was 1.07 MPa and without nodia was 0.91 MPa, while the embedded length of 75 mm with nodia was 1.39 MPa and without nodia was 0.94 MPa.